The Language Diamond: An Intercultural Model to Teach and Learn (through) Languages - Nathalie Auger (MDPI AG, 2023)
The starting point (1) of our proposal is the observation of the lack of intercultural practices in schools in France, even in the crucial context of teaching French to migrant children (2). Thanks to previous studies, we, therefore, develop theoretical anchors (3) about learning territories, the ways to recycle language, and cultural experiences that can encompass all the context parameters (a pan-language approach) to elaborate an intercultural model for learning and teaching. The aim is to propose, methodological reflections to offer a model which could help change the representations and practices of the educational community regarding multilingualism so that students' language and cultural experiences could become an asset to achieve academic success (4). It leads to a discussion about leads to the creation of the intercultural language diamond model to teach and learn (through) languages (5). Projects based on the language model give the opportunity to discuss this proposal (5): interests and possible limitations (6). The conclusion (7) pledges the use of the language diamond to counterbalance the ideology which considers diversity as an issue, and therefore adopt a holistic, maximalist point of view: a pan-language and pan-cultural approach to encompass the complexity of education challenges today.